Implementation of Service Oriented Architecture in Cloud Computing for Periodic Salary Increment - Khairunnisa Saragih; Eko Darwiyanto; Hetti Hidayati (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2020)
Technological advances are used to help improve government performance in matters relating to the use of technology in the process of Periodic Salary Increment, which is the task of the sub-division of staffing at the Regional Government Forestry Service Office of West Java Province. Judging from the document for Standard Operating Procedures (SOP) for the subdivision of the West Java Provincial Government Forestry Service office in 2018, in the work process section of periodic salary increases with stages that require time and energy so that the performance process appears less effective. So that it implements a system that can complete the periodic salary work process using the Cloud Computing-based Service-Oriented Architecture (SOA) method. The purpose of using cloud computing is to increase reliability and flexibility without increasing computing costs. Cloud computing has become a solution and opportunity for the development of the Information and Communication Technology (ICT) industry to get better advantages over other technologies. On the other hand, the user does not need to see or have knowledge of the physical location and system configuration of the service. This research resulted in the performance of the sub-division of the staffing of the West Java Provincial Government Forestry Service in the process of making regular salary increases more effective. And from the test can prove that 74.74% of the questions answered